The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s12889-018-5740-y
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid symptoms of depression and musculoskeletal pain and risk of long term sickness absence

Abstract: BackgroundSymptoms of depression and musculoskeletal pain have both been found to be associated with increased risk of long term sickness absence (LTSA). The comorbidity between depression and pain i.e. simultaneous presence of both symptoms, is well established in the literature. The aim for the current investigation was to investigate whether the presence of comorbid pain influences the associations between depressive symptoms and LTSA or if the presence of comorbid depressive symptoms influences association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…A 10‐year (5 plus 5 year) follow‐up of metal industry employees found reciprocal longitudinal associations between distress symptoms and musculoskeletal pain, whereas depressive symptoms were predictive of pain in men but not in women (Leino & Magni, ). In predicting long‐term sickness absences, an interaction between depressive symptoms and musculoskeletal pain was found among female Danish employees (Melkevik et al, ). Among Finnish employees, the risk of disability retirement was fourfold in those with co‐occurring mental and musculoskeletal disorders compared to participants with neither, while having either disorder alone was associated with a twofold risk (Kaila‐Kangas et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10‐year (5 plus 5 year) follow‐up of metal industry employees found reciprocal longitudinal associations between distress symptoms and musculoskeletal pain, whereas depressive symptoms were predictive of pain in men but not in women (Leino & Magni, ). In predicting long‐term sickness absences, an interaction between depressive symptoms and musculoskeletal pain was found among female Danish employees (Melkevik et al, ). Among Finnish employees, the risk of disability retirement was fourfold in those with co‐occurring mental and musculoskeletal disorders compared to participants with neither, while having either disorder alone was associated with a twofold risk (Kaila‐Kangas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain and neck pain are the most prevalent and affect people of all age groups (GBD 2017 Disease and Injury Incidence and Prevalence Collaborators, ). Musculoskeletal pain occurs in several body sites concurrently more often than in a single site only in the general population (Carnes et al, ; Schmidt & Baumeister, ), among the occupationally active (Melkevik et al, ; Saastamoinen, Leino‐Arjas, Laaksonen, Martikainen, & Lahelma, ) and among older adults (Butera et al, ). While musculoskeletal pain in adolescence often persists to midlife (Leino‐Arjas et al, ) and midlife pain to old age (Neupane et al, ), the widespreadness of pain may decrease with retirement from work (Neupane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 264 million people worldwide are affected [32]. Besides being a serious disorder itself, depression is also a major predictor of other healthrelated outcomes like cardiovascular events, treatment noncompliance, musculoskeletal pain, absenteeism, dementia, and suicide [16,20,21,45]. Accordingly, the Global Burden of Disease Study of the World Health Organization estimates that depression is one of the leading causes of disability [34,54].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the comorbidity of MSDs and depression was 14.5% in the study sample. A previous study with over 6,500 Danish female health care workers reported an 18% comorbidity including one or more musculoskeletal pain locations and medium or higher levels of depressive symptoms (Melkevik et al, 2018). The comorbid pain and depression have been widely reported in the patient population (Goesling et al, 2013).…”
Section: Discussionmentioning
confidence: 99%